2002
DOI: 10.1029/2001jd000974
|View full text |Cite
|
Sign up to set email alerts
|

Climate/chemistry effects of the Pinatubo volcanic eruption simulated by the UIUC stratosphere/troposphere GCM with interactive photochemistry

Abstract: The influence of the sulfate aerosol formed following the massive Pinatubo volcanic eruption in June 1991 on the chemical composition, temperature, and dynamics of the atmosphere has been investigated with the University of Illinois at Urbana‐Champaign (UIUC) stratosphere–troposphere General Circulation Model (GCM) with interactive photochemistry (ST‐GCM/PC). Ensembles of five runs have been performed for the unperturbed (control) and perturbed (experiment) conditions. The simulated repartitioning within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 43 publications
5
62
0
Order By: Relevance
“…In addition, a relatively large minimum occurs in 1993; this minimum follows the 15 June 1991 eruption of Mt. Pinatubo and is caused mainly by the chemical and/or dynamical effects of this aerosol injection event (Hadjinicolaou et al 1997;Stenchikov et al 2002;Rozanov et al 2002). At the latitudes plotted in Fig.…”
Section: Ozone Interannual Variability and Trends At Northern Midlatimentioning
confidence: 99%
“…In addition, a relatively large minimum occurs in 1993; this minimum follows the 15 June 1991 eruption of Mt. Pinatubo and is caused mainly by the chemical and/or dynamical effects of this aerosol injection event (Hadjinicolaou et al 1997;Stenchikov et al 2002;Rozanov et al 2002). At the latitudes plotted in Fig.…”
Section: Ozone Interannual Variability and Trends At Northern Midlatimentioning
confidence: 99%
“…Graf et al, 1993;Kirchner et al, 1999;Rozanov, 2002;Shindell et al, 2001), assessments of the multi-model ensembles of the Coupled Model Intercomparison Projects (CMIP) 3 and 5 showed no significant winter warming response to prescribed volcanic forcing, nor did they show significant anomalies in post-eruption dynamical quantities in the stratosphere or at the surface (Driscoll et al, 2012;Stenchikov et al, 2006). It has been suggested that in order for a model to successfully respond to volcanic forcing, it should include a reasonably well-resolved stratosphere (Shindell, 2004;Stenchikov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, separating the different sources of ozone variability is crucial for understanding the global ozone response to varying anthropogenic emissions and climate change (e.g., Austin and Wilson 2006;Hess and Lamarque 2007;Li et al 2009;Frossard et al 2013;Rieder et al 2013). Numerous previous studies have analyzed the stratospheric ozone variability caused by external processes such as the solar cycle (e.g., Chandra and McPeters 1994;Rozanov et al 2005;Dhomse et al 2006) and volcanic aerosols (e.g., Hofmann and Oltmans 1993;Solomon et al 1996;Rozanov et al 2002;Dhomse et al 2015), which can induce considerable variation in ozone over both short and long periods. TOC variations can also be caused by changes in the surface climate ).…”
Section: Introductionmentioning
confidence: 99%